Antibacterial wollastonite supported excellent proliferation and osteogenic differentiation of human bone marrow derived mesenchymal stromal cells - Venkatraman, Senthil Kumar; Choudhary, Rajan; Genasan, Krishnamurithy; Murali, Malliga Raman; Raghavendran, Hanumantha Rao Balaji; Kamarul, Tunku; Suresh, Anushree; Abraham, Jayanthi; Venkateswaran, Seshasailam; Livingston, Abel; Swamiappan, Sasikumar (Journal of sol-gel science and technology, 2021)
Biocompatibility and bacterial infections are the primary concerns associated with the current bone graft substitutes. The application of wollastonite-based scaffolds for bone tissue engineering becomes a novel subject of interest. In the present study, a single phasic wollastonite scaffold was synthesised using citric acid-based sol–gel combustion route. Its physicochemical characteristics, antibacterial properties as well as its biocompatibility and osteogenic induction effect on human bone marrow derived stromal cells ( hBMSCs ) are yet to be explored. The TGA/DTA, XRD and SEM/EDX confirmed the characteristics of wollastonite. The antibacterial test indicated wollastonite inhibition of 47.81% and 45.54% for gram-positive, Staphylococcus aureus and Staphylococcus epidermidis and 47.04% and 46.07% for gram-negative, Escherichia coli and Pseudomonas aeruginosa bacterial strains, respectively. The SEM micrographs demonstrated an excellent attachment of hBMSCs on wollastonite and comparable to commercial hydroxyapatite (cHA) scaffold. The alamar blue cell proliferation assay confirmed 1.7- and 1.8-fold significant increase in hBMSCs seeded on wollastonite and cHA scaffold, respectively, on day 14 as compared with day 1. The immunohistochemistry analysis on Type-I collagen (Col1) and Bone morphogenetic protein-2 (BMP2) expression on day 14 confirmed the osteogenic differentiation of hBMSCs seeded on wollastonite and comparable with cHA scaffold. In conclusion, wollastonite scaffold has a greater potential to substitute bone grafts in orthopaedic applications.